Pengaruh Aromaterapi Peppermint dan Terapi Relaksasi Benson terhadap Saturasi Oksigen Pasien Bronkopneumonia - Naning Setyo Wati; Retno Setyawati; Suyanto Suyanto (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Bronchopneumonia is an infectious disease that attacks the lower respiratory system, including the bronchioles and alveoli, charactherized by the presence of spots or patches on the lung lobes caused by Staphylococcus aereus bacteria in mild cases and followed by Klebsiella pneumoniae in severe cases. On of the non-pharmacological therapies for bronchopneumonia is peppermint aromatherapy and benson relaxation therapy. Peppermint aromatherapy has the effect of relieving the nose and making breathing easier combined with the benson relaxation technique which ultimately effects oxygen saturation. This study aims to determine the effect of administering peppermint aromatherapy and benson relaxation therapy on oxygen saturation levels in bronchopneumonia patients. This study used a quasi experimental design with a one group pre-post test design, involving 17 respondents selected through purposive sampling. The results of this study showed that there was a difference in oxygen saturation before and after the intervention with a p-value of 0.0001 < 0.05. The administration of peppermint aromatherapy and benson relaxation therapy influences the increase in oxygen saturation of broncopneumonia patients at RSI Sultan Agung Semarang.